If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -3 + 5x = 4 + 4x + 1 Reorder the terms: -3 + 2x + 5x = 4 + 4x + 1 Combine like terms: 2x + 5x = 7x -3 + 7x = 4 + 4x + 1 Reorder the terms: -3 + 7x = 4 + 1 + 4x Combine like terms: 4 + 1 = 5 -3 + 7x = 5 + 4x Solving -3 + 7x = 5 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -3 + 7x + -4x = 5 + 4x + -4x Combine like terms: 7x + -4x = 3x -3 + 3x = 5 + 4x + -4x Combine like terms: 4x + -4x = 0 -3 + 3x = 5 + 0 -3 + 3x = 5 Add '3' to each side of the equation. -3 + 3 + 3x = 5 + 3 Combine like terms: -3 + 3 = 0 0 + 3x = 5 + 3 3x = 5 + 3 Combine like terms: 5 + 3 = 8 3x = 8 Divide each side by '3'. x = 2.666666667 Simplifying x = 2.666666667
| 2x+y-2z=2 | | s^2+9s+81=0 | | 7*6= | | 89-7x=29x+21 | | X^3=81x | | x-4y+2z=-11 | | 26=7x+x+2 | | 30-5a=10 | | -.5(y+5)=-1 | | c/8+10=15 | | 3x+2y-4z=3 | | c/8=15 | | 12x^2+12x-24=0 | | 12-10x=62-24x | | -7(x+1)=2x-34 | | 24a-22=-4(1-6n) | | -x+3=-3x+11 | | 4x^2-48+44=0 | | x^2+36x=144 | | 6x-3=2x+5 | | 9x(3x)2x= | | 8x+9+2(10+x)=2x+29 | | 0.4x-0.6x-5=1 | | x=35 | | x^2+36x-144=0 | | -.33m-7=5 | | 26x-2-13x=10x+5+3x | | 29x-7-11x=15x+9+3x | | x^2+3x-9=3x | | 6x-4(x+7)=5+2(x+6) | | 2x-5=9+8x | | 1.6x-4(x+7)=5+2(x+6) |